2016
DOI: 10.1097/dcr.0000000000000577
|View full text |Cite
|
Sign up to set email alerts
|

Risk of Surgical Site Infection Varies Based on Location of Disease and Segment of Colorectal Resection for Cancer

Abstract: Rectal resections for cancer are independently associated with an increased likelihood of superficial, deep, and organ space infections. The policy on surgical site infections as a quality measure currently in place requires modification to adjust for the location of pathology and, hence, the anatomical segment resected when assessing the risk for type of surgical site infection.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
18
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(22 citation statements)
references
References 24 publications
3
18
1
Order By: Relevance
“…Further studies are required to elucidate whether OAs confer a protective effect for organ space infection in rectal resections with an anastomosis. Risk factors reported in the literature for SSIs following colorectal surgery include diagnosis, laparoscopic vs open procedure, location (colonic vs rectal), stoma creation, blood transfusion, smoking, alcohol use, diabetes, operative time and preoperative radiation for rectal cancers [12,[23][24][25][26][27][28]. Our multivariate analysis found that operative approach (open vs laparoscopic) and OAs were significant predictors of SSI, a similar finding to other studies [23,24,26].…”
Section: Discussionsupporting
confidence: 86%
“…Further studies are required to elucidate whether OAs confer a protective effect for organ space infection in rectal resections with an anastomosis. Risk factors reported in the literature for SSIs following colorectal surgery include diagnosis, laparoscopic vs open procedure, location (colonic vs rectal), stoma creation, blood transfusion, smoking, alcohol use, diabetes, operative time and preoperative radiation for rectal cancers [12,[23][24][25][26][27][28]. Our multivariate analysis found that operative approach (open vs laparoscopic) and OAs were significant predictors of SSI, a similar finding to other studies [23,24,26].…”
Section: Discussionsupporting
confidence: 86%
“…A recent pooled analysis of comparative studies in laparoscopic CRC surgery has identified BMI ≥ 30 kg/m 2 as a risk factor for paralytic ileus (p = 0.02), urologic morbidity (p = 0.03), surgical site infection (p < 0.001), and anastomotic leakage (p = 0.02) . A review of 45,956 CRC surgeries showed that risk of postoperative infection varies based on location of disease and segment of colorectal resection for cancer, with rectal resection independently associated with an increased likelihood of superficial, deep, and organ space infections . The accumulation of blood or serum in the surgical wound resulting in the formation of hematomas, seromas, and dead spaces can cause the incision to separate and predispose to wound infection, since bacteria can gain access to deeper layers and multiply uninhibited in the stagnant fluid…”
Section: Discussionmentioning
confidence: 99%
“…As such, it therefore seems appropriate to analyse treatment outcomes separately. Many studies have found that SSI occurs more frequently in rectal cancer patients undergoing surgery than in those being operated for colonic cancer [11][12][13][14]17]. A study by Konishi et al on 556 patients after large bowel resection found that in those post-rectal resection, SSI occurred twice more frequently compared to patients who had undergone colonic resection, (i.e.…”
Section: Discussionmentioning
confidence: 99%
“…The incidence of SSI following rectal cancer surgery widely varies, ranging from 7.6% to 26.7% [10][11][12][13][14][15][16]. Such cancer surgery is technically more demanding than colonic surgery, as patients are frequently after neoadjuvant radiotherapy and that operation times are usually longer.…”
Section: Discussionmentioning
confidence: 99%